2020
DOI: 10.1021/acs.est.0c00767
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Fractionation during Biotransformation of Chiral Pharmaceuticals in Recirculating Water-Sediment Test Flumes

Abstract: Many organic contaminants entering the aquatic environment feature stereogenic structural elements that give rise to enantiomerism. While abiotic processes usually act identical on enantiomers, biotic processes, such as biodegradation often result in enantiomeric fractionation (EFr), i.e. the change of the relative abundance of enantiomers. Therefore, EFr offers the opportunity to differentiate biodegradation in complex environmental systems from abiotic processes. In this study, an achiral-chiral two-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…This may explain the higher bacterial abundance and diversity detected in the incubated surface sediment samples (Figures 2 and 3). High diversity and abundance have been previously associated with enhanced biotransformation efficiency of many organic micropollutants [16,23,[32][33][34][35], an observation the current study extends.…”
Section: Influence Of Toc On Biotransformation and Sorption Of Trocssupporting
confidence: 75%
“…This may explain the higher bacterial abundance and diversity detected in the incubated surface sediment samples (Figures 2 and 3). High diversity and abundance have been previously associated with enhanced biotransformation efficiency of many organic micropollutants [16,23,[32][33][34][35], an observation the current study extends.…”
Section: Influence Of Toc On Biotransformation and Sorption Of Trocssupporting
confidence: 75%
“…Our findings are consistent with previous studies conducted in situ on the same river that reported both biodegradation and sorption as the critical attenuation mechanisms for metoprolol in the hyporheic zone (Posselt et al 2018;Schaper et al 2019). Similar findings were reported in water-sediment recirculating flumes and sediment microcosms (Mechelke et al 2020;Posselt et al 2020;Rutere et al 2020a). The significant contribution of biodegradation in the removal of metoprolol has further been demonstrated in other diverse matrices such as riverbank filtration systems, WWTPs, subsurface flow constructed wetlands, biological activated carbon systems, and surface water (Abromaitis et al 2016;Li and McLachlan 2019;Rubirola et al 2014;Rühmland et al 2015;Schmidt et al 2007).…”
Section: Microbial Degradation As An Important Removal Mechanism Of Metoprolol In Hyporheic Zone Sedimentssupporting
confidence: 93%
“…In previous studies we described the experiment, in which in total 20 river-simulating flumes were set up to investigate the influence of bacterial diversity and hyporheic exchange on the fate of organic micropollutants in the SW. The previous studies addressed the complete setup and functioning of the experimental design 35 , the fate of micropollutants and the individual influence of the treatments in the SW 36 , 37 , and a hydrodynamic model estimating hyporheic exchange in the flumes 38 . The present study focuses on the transformation of micropollutants in the hyporheic zone, i.e.…”
Section: Introductionmentioning
confidence: 99%